2005
DOI: 10.1111/j.1529-8817.2005.04011.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF OSTREOPSIS AND COOLIA (DINOPHYCEAE) ISOLATES IN THE WESTERN MEDITERRANEAN SEA BASED ON MORPHOLOGY, TOXICITY AND INTERNAL TRANSCRIBED SPACER 5.8S rDNA SEQUENCES1

Abstract: Several isolates of epiphytic dinoflagellates belonging to the genera Ostreopsis Schmidt and Coolia Meunier from the western Mediterranean Sea were examined by LM and EM, toxicity assays, and internal transcribed spacer (ITS) regions of nuclear rDNA, and 5.8S rDNA were sequenced. Morphological comparisons based on the analyses of cell shape, size, thecal plates, and surface ornamentation revealed two distinct species in the western Mediterranean: O. cf. siamensis Schmidt from the Catalan, Andalusian, and Sicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
253
4
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(294 citation statements)
references
References 58 publications
28
253
4
9
Order By: Relevance
“…Two main clades of Coolia were consistently well supported in the phylogenetic tree, one including the strains of C. monotis plus C. malayensis as sister taxon, and the other the strains of C. canariensis. In agreement with the results of Penna et al (2005), only slight geographical differences can be observed among the different strains from the Mediterranean and the local isolates of C. monotis, which appear to belong to a single evolutionary lineage, whereas the New Zealand strain constitutes a genetically distinct entity described as Coolia malayensis (Leaw et al, 2010). Similar relationships were inferred by Fraga et al (2008) who found three different lineages within selected strains of the genus Coolia, one of them including strains of C. canariensis, a second with C. monotis from Indonesia and Belize and a third containing two sister groups, one corresponding to C. monotis from European localities and the other to C. monotis and C. malayensis from New Zealand, Malaysia and Florida.…”
Section: Phylogenysupporting
confidence: 82%
See 4 more Smart Citations
“…Two main clades of Coolia were consistently well supported in the phylogenetic tree, one including the strains of C. monotis plus C. malayensis as sister taxon, and the other the strains of C. canariensis. In agreement with the results of Penna et al (2005), only slight geographical differences can be observed among the different strains from the Mediterranean and the local isolates of C. monotis, which appear to belong to a single evolutionary lineage, whereas the New Zealand strain constitutes a genetically distinct entity described as Coolia malayensis (Leaw et al, 2010). Similar relationships were inferred by Fraga et al (2008) who found three different lineages within selected strains of the genus Coolia, one of them including strains of C. canariensis, a second with C. monotis from Indonesia and Belize and a third containing two sister groups, one corresponding to C. monotis from European localities and the other to C. monotis and C. malayensis from New Zealand, Malaysia and Florida.…”
Section: Phylogenysupporting
confidence: 82%
“…The tabulation pattern of C. canariensis is very similar to that of C. areolata, but thecal ornamentation allows differentiation of the two species. Cell sizes of C. monotis strains fall within published values (Penna et al, 2005;Dolapsakis et al, 2006). The strains have morphological features similar to previous descriptions of the species, although with some differences from Meunier's (1919) original description and other later descriptions, especially regarding some plates of the epitheca.…”
Section: Taxonomic Remarkssupporting
confidence: 66%
See 3 more Smart Citations